Albumin conjugates and assemblies as versatile bio-functional additives and carriers for biomedical applications. Issue 3 (20th November 2018) - Tao, Chao; Chuah, Yon Jin; Xu, Chenjie; Wang, Dong-An
Abstract : As the most abundant plasma protein, serum albumin has been extensively studied and employed for therapeutic applications. Abstract : As the most abundant plasma protein, serum albumin has been extensively studied and employed for therapeutic applications. Despite its direct clinical use for the maintenance of blood homeostasis in various medical conditions, this review exclusively summarizes and discusses albumin-based bio-conjugates and assemblies as versatile bio-functional additives and carriers in biomedical applications. As one of the smallest-sized proteins in the human body, albumin is physiochemically stable and biochemically inert. Moreover, albumin is also endowed with abundant specific binding sites for numerous therapeutic compounds, which also endow it with superior bioactivities. Firstly, due to its small size and binding specificity, albumin alone or its derived assemblies can be utilized as competent drug carriers, which can deliver drugs through the enhanced permeability and retention (EPR) effect or actively target lesion sites through binding with gp60 and secreted protein acidic and rich in cysteine (SPARC) in tumor sites. Furthermore, its biochemical stability and inertness make it a safe and biocompatible coating material for use in biomedical applications. Albumin-based surface modifying additives can be used to functionalize both macro substrates ( e.g. surfaces of medical devices or implants) and nanoparticle surfaces ( e.g. drug carriers and imaging contrast agents). In this review, we elaborate on the synthesis and applications of albumin-based bio-functional coatings and drug carriers, respectively.